Nutritional deficiency in scarlet eggplant limits its growth by modifying the absorption and use efficiency of macronutrients - Teixeira, Gelza Carliane Marques [UNESP]; De Mello Prado, Renato [UNESP]; Oliveira, Kamilla Silva [UNESP]; Buchelt, Antonio Carlos; Rocha, Antonio Márcio Souza [UNESP]; De Souza Santos, Michelle [UNESP] (My University, 2021)
The intensity damages caused by nutritional deficiency in growing plants can vary with nutrients. The effects caused by nutrient omission in the plant nutritional efficiency in relation to the absorption and use of the missing nutrient, and the reasons why these damages reflect in other nutrients have not yet been reported in the culture of scarlet eggplant. A better understanding of the nutritional mechanisms involved may clarify why certain nutrients cause greater limitations than other during plants growth. Thus, this study was designed with the aim of evaluating the damages caused by macronutrients deficiency in the culture of scarlet eggplant in the accumulation of these nutrients, nutritional deficiency, plants growth and in visual symptoms. The experiment was carried out in a controlled environment where plants were cultivated in a hydroponic system. Treatments consisted of supplying a complete Hoagland and Arnon solution (CS), and other nutrient solutions with individual omissions of nitrogen (-N), phosphorus (-P), potassium (-K), calcium (-Ca), magnesium (-Mg) and sulphur (-S). When a nutrient deficiency arose, nutritional analyses, growth and visual symptoms were analyzed. The omissions of N, S and K in the nutrient solution resulted in lower accumulation of all macronutrients in both the above and below ground biomass. Individual omissions resulted in nutritional imbalances with reflexes in the absorption efficiencies and use of the missing nutrient, as well as of other nutrients, revealing that the metabolism involves multiple nutritional interactions. Losses of nutritional efficiencies of macronutrients caused detrimental effects on plants growth, with reduced height, stem diameter, number of leaves, leaf area, and biomass production in above ground and below ground. From the losses in production in above ground biomass, the order of macronutrients limitation was N, S, K, Ca, Mg, and P, with reductions of 99, 96, 94, 76, 51 and 46%, respectively, in comparison to plants cultivated in CS. The most limiting nutrients were N, S, and K, seen that its deficiencies affected the metabolism of all other nutrients. This study demonstrates the importance of an adequate nutritional management of N, S, and K in the cultivation of scarlet eggplant.